PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS KAHOOT DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMP ISLAM AL-WASI KABUPATEN MAROS - Nurwahidah; Mustamin; Subaedah; Bunyamin, Andi; Sampurno, Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the increase in student learning motivation through the application of Kahoot-based interactive learning media in the subject of Islamic Religious Education for class VIII of SMP Islam Al-Wasi', Maros Regency. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of two cycles, namely planning, action implementation, observation, and reflection. The research subjects were 32 class VIII students. Data collection techniques included observation, interviews, tests, questionnaires, and documentation. Data analysis was carried out qualitatively descriptively and quantitatively using average and percentage calculations. The results showed that the application of Kahoot-based interactive learning media was able to increase student learning motivation. In Cycle I, the results of observations of learning motivation reached a percentage of 82.50% with a good category, then increased in Cycle II to 91.25% with a very good category. The increase in learning motivation has an impact on student learning outcomes. The average value of learning outcomes increased from 41.25 in the pre-cycle stage to 79.06 in Cycle I, then increased again to 86.56 in Cycle II. The percentage of learning completion also increased from 0% in the pre-cycle to 65.63% in Cycle I and 90.63% in Cycle II, thus exceeding the research success indicator, namely at least 80% of students achieving the Minimum Completion Criteria (KKM). Based on the results of the study, it can be concluded that the application of Kahoot-based interactive learning media is effective in increasing student learning motivation which has a positive impact on improving learning outcomes in the subject of Islamic Religious Education for class VIII of SMP Islam Al-Wasi', Maros Regency. Kahoot media can be used as an innovative, interactive, and fun learning alternative to improve the quality of the learning process.